MANAGING SPORT FOR HEALTHY LIFESTYLE: A BRIEF REVIEW AND FUTURE RESEARCH DIRECTIONS - Yudha Gusti Wibowo (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2019)
Background: Monotone activities and lack of physical activity are problems in recent decades. These phenomena will give negative impact for human health such as some disease. This problems can solve by sports Purpose: The purpose of this article is to find sports impact for human health. Results: Result of this study are sports can solve some disease because sports is medicine, sport can support mental health recovery and sport is physical activities for supporting healthy lifestyle Conclusion: Sports is an important activity in human life